2015
DOI: 10.1016/j.ijid.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

An association study of NRAMP1, VDR, MBL and their interaction with the susceptibility to tuberculosis in a Chinese population

Abstract: Our study suggests that genotypes of many polymorphic genes are associated with TB, it is necessary to further explore the mechanism of genotypes and gene-gene interaction in susceptibility to tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 29 publications
0
27
2
Order By: Relevance
“…We noted that Wu et al . have reported that LYPB haplotype was associated with TB in southern Chinese23. However, frequencies of MBL2 haplotypes in Wu’s study were remarkably different from those in Chinese subjects observed in other studies.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…We noted that Wu et al . have reported that LYPB haplotype was associated with TB in southern Chinese23. However, frequencies of MBL2 haplotypes in Wu’s study were remarkably different from those in Chinese subjects observed in other studies.…”
Section: Discussioncontrasting
confidence: 72%
“…These studies have small sample size, usually involving about 200 or less PTB patients of Chinese origin1920212223, which might lead to artificial associations. In addition, the four functional SNPs in the MBL2 gene is in linkage disequilibrium (LD) and more appropriate to be investigated together (in both haplotype and haplotype pairs).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the online database search, the references given in the screened articles were also reviewed for other potential studies. Lastly, after cautious screening and following the pre-set inclusion and exclusion criteria for the selection of the studies, a total of 22 research publications11121314151617181920212223242526272829303132, showing case-control studies comprising of a total of 7095 confirmed TB patients and 7662 control subjects were included in this pooled analysis (Fig. 1 PRISMA Flow-diagram).…”
Section: Resultsmentioning
confidence: 99%